Anemia and Bone Marrow Suppression After Intra-Arterial Chemotherapy in Children With Retinoblastoma: A Retrospective Analysis - Zeng, Changjuan; Han, Minglei; Fan, Jiayan; He, Xiaoyu; Jia, Renbing; Li, Li; Wen, Xuyang; Song, Xuefei; Hou, Lili (Frontiers in Oncology, 2022)
Background Retinoblastoma (Rb) is a common ocular malignant tumor in children. Intra-arterial chemotherapy (IAC) has been widely used in children with Rb and has achieved an ideal therapeutic effect. However, IAC has side effects, including anemia and bone marrow suppression, for which explicit evidence on the risk factors is lacking. This study aimed to evaluate the covariates that may affect the occurrence of anemia and bone marrow suppression in children with Rb after IAC. Methods Children with Rb admitted between May 2019 and January 2021 were included into the study. The differences in the number of children with anemia and bone marrow suppression before and after IAC according to different covariates were recorded. All potential impact factors were included into the univariate and multivariate regression models to identify the related covariates of post-IAC anemia and bone marrow suppression. Results Data of 282 children with Rb were retrospectively collected. After IAC, children with Rb had increased severities of anemia (p <0.0001, chi-square test) and bone marrow suppression (p = 0.001, chi-square test). Moreover, the number of children with Rb who had an increased cross-level change in the severity of anemia and degree of bone marrow suppression was 80 (41.24%) and 64 (32.49%), respectively. The univariate regression analysis showed that numerous factors (such as pre-IAC intravenous chemotherapy, results of pre-IAC routine blood tests, and some serological indicators for liver and kidney function) affected the anemia severity and degree of bone marrow suppression in children with Rb after IAC. Additionally, the predictive model of the multivariate regression could predict anemia and bone marrow suppression. Conclusion Children with Rb may have an increased risk of anemia and bone marrow suppression after IAC, but this is temporary and can be influenced by several factors. Therefore, IAC should be maintained as the standard of care. We generated predictive equations for predicting anemia severity and degree of bone marrow suppression, which can guide the prediction and timely control of anemia and bone marrow suppression after IAC.